Fracture Mechanics Properties, Patterns and Behaviours - Maximo Alves, Lucas (IntechOpen, 2016)
This book is a collection of 13 chapters divided into seven sections: Section I: "General Foundations of the Stress Field and Toughness" with one chapter, Section II: "Fractography and Impact Analysis" with two chapters, Section III: "Toughness Fracture" with three chapters, Section IV: "Fracture Behavior" with two chapters, Section V: "Natural and Hydraulic Fractures" with two chapters, section VI: "Fatigue" with one chapter and Section VII: "Fracture Biomaterials and compatible" with two chapters. This book covers a wide range of application of fracture mechanics in materials science, engineering, rock prospecting, dentistry and medicine. The book is aimed towards materials scientists, metallurgists, mechanical and civil engineers, doctors and dentists and can also be well used in education, research and industry.